2005
DOI: 10.1111/j.1365-2826.2005.01273.x
|View full text |Cite
|
Sign up to set email alerts
|

Short Day Lengths Enhance Skin Immune Responses in Gonadectomised Siberian Hamsters

Abstract: In Siberian hamsters and other photoperiodic rodents, exposure to short photoperiods simultaneously inhibits gonadal hormone secretion and enhances some measures of immune function. The present study tested whether gonadal hormones mediate the effects of short days on skin immune function (delayed-type hypersensitivity reactions) in male Siberian hamsters. The magnitude of delayed-type hypersensitivity reactions was greater in hamsters exposed to short days relative to those in long days. Comparable effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 43 publications
5
21
0
Order By: Relevance
“…Increases in the number of cells expressing CD62 cell-surface markers-adhesion molecules that participate in the migration of lymphocytes through endothelium-could contribute to enhanced skin inflammatory responses in SD (7,12). Thus, earlier reports, suggesting gonadal hormone independence of skin inflammatory responses (39), are consistent with the persistence of photoperiodic differences in CD62ϩ cells following gonadectomy in the present study. Studies in other reproductively photoperiodic rodents have likewise indicated several gonadal hormone-independent effects of photoperiod on the immune system (16).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Increases in the number of cells expressing CD62 cell-surface markers-adhesion molecules that participate in the migration of lymphocytes through endothelium-could contribute to enhanced skin inflammatory responses in SD (7,12). Thus, earlier reports, suggesting gonadal hormone independence of skin inflammatory responses (39), are consistent with the persistence of photoperiodic differences in CD62ϩ cells following gonadectomy in the present study. Studies in other reproductively photoperiodic rodents have likewise indicated several gonadal hormone-independent effects of photoperiod on the immune system (16).…”
Section: Discussionsupporting
confidence: 81%
“…Data bearing on this issue have not yielded consistent results. In hamsters, photoperiodic changes in antibody production and skin inflammatory responses occur independent of changes in the reproductive system (18,39); in contrast, other indices of immunity more closely track gonadal condition (spontaneous blastogenesis, leukocyte concentrations) (41,45). Determining the extent to which seasonal changes in the immune system depend on concurrent changes in the reproductive system remains a key step toward understanding how photoperiod drives seasonal immunity, and more generally, may provide insight into how neuroendocrine activity impinges on the immune system.…”
mentioning
confidence: 99%
“…Indeed, gonadal androgens influence immune function-often in an immunosuppressive fashion (Klein, 2000;Obendorf and Patchev, 2004;Mueh-lenbein and Bribiescas, 2005). However, in Siberian hamsters, several experiments have indicated that photoperiodic changes in immune function can occur independent of changes in reproductive system (blastogenesis: Prendergast et al, 2002b;leukocyte counts: Prendergast et al, 2004a; skin inflammatory responses: Prendergast et al, 2005). Studies in other reproductively photoperiodic species have indicated similar gonadal hormone-independent effects of photoperiod on the immune system (Demas and Nelson, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Further, because oestrogens tend to enhance immune activity, if photoperiodic changes in immune function are mainly due to fluctuations in sex steroid hormones, then females in short days that have low oestrogen concentrations should show reduced immune function when compared with long-day animals (or at least not exhibit male-like increases). Because these predictions were not substantiated in male and female deer mice ) and gonadectomy and exogenous testosterone administration did not alter short-day enhancement of the DTH response in Siberian hamsters (Prendergast et al 2005), this hypothesis has fallen out of favour.…”
Section: Proximate Mechanisms Mediating Trade-offsmentioning
confidence: 96%